Type 1 Diabetes Mellitus in the SARS-CoV-2 Pandemic: Oxidative Stress as a Major Pathophysiological Mechanism Linked to Adverse Clinical Outcomes - Aikaterini Kountouri; Emmanouil Korakas; Ignatios Ikonomidis; Athanasios Raptis; Nikolaos Tentolouris; George Dimitriadis; Vaia Lambadiari (MDPI AG, 2021)
Recent reports have demonstrated the association between type 1 diabetes mellitus (T1DM) and increased morbidity and mortality rates during coronavirus disease (COVID-19) infection, setting a priority of these patients for vaccination. Impaired innate and adaptive immunity observed in T1DM seem to play a major role. Severe, life-threatening COVID-19 disease is characterized by the excessive release of pro-inflammatory cytokines, known as a "cytokine storm". Patients with T1DM present elevated levels of cytokines including interleukin-1a (IL), IL-1β, IL-2, IL-6 and tumor necrosis factor alpha (TNF-α), suggesting the pre-existence of chronic inflammation, which, in turn, has been considered the major risk factor of adverse COVID-19 outcomes in many cohorts. Even more importantly, oxidative stress is a key player in COVID-19 pathogenesis and determines disease severity. It is well-known that extreme glucose excursions, the prominent feature of T1DM, are a potent mediator of oxidative stress through several pathways including the activation of protein kinase C (PKC) and the increased production of advanced glycation end products (AGEs). Additionally, chronic endothelial dysfunction and the hypercoagulant state observed in T1DM, in combination with the direct damage of endothelial cells by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), may result in endothelial and microcirculation impairment, which contribute to the pathogenesis of acute respiratory syndrome and multi-organ failure. The binding of SARS-CoV-2 to angiotensin converting enzyme 2 (ACE2) receptors in pancreatic b-cells permits the direct destruction of b-cells, which contributes to the development of new-onset diabetes and the induction of diabetic ketoacidosis (DKA) in patients with T1DM. Large clinical studies are required to clarify the exact pathways through which T1DM results in worse COVID-19 outcomes.